2021
DOI: 10.3389/fbioe.2021.780197
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous PEDOT-Carbon Composite on Flexible Probes for Soft Neural Interfacing

Abstract: In this study, we report a flexible implantable 4-channel microelectrode probe coated with highly porous and robust nanocomposite of poly (3,4-ethylenedioxythiophene) (PEDOT) and carbon nanofiber (CNF) as a solid doping template for high-performance in vivo neuronal recording and stimulation. A simple yet well-controlled deposition strategy was developed via in situ electrochemical polymerization technique to create a porous network of PEDOT and CNFs on a flexible 4-channel gold microelectrode probe. Different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…For example, combining conducting polymer Poly (3,4-ethylenedioxythiophene) (PEDOT) with carbon-based nanomaterials with high mechanical hardness can prevent PEDOT films from deforming and cracking after long-term operation [ 65 ]. Recently, Vajrala et al [ 66 ] fabricated novel nanocomposites of highly porous and robust PEDOT-CNF by a simple and reproducible electrodeposition method ( Figure 1 d), and the experimental results showed that it has superior performance to pure PEDOT materials.…”
Section: Microelectrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, combining conducting polymer Poly (3,4-ethylenedioxythiophene) (PEDOT) with carbon-based nanomaterials with high mechanical hardness can prevent PEDOT films from deforming and cracking after long-term operation [ 65 ]. Recently, Vajrala et al [ 66 ] fabricated novel nanocomposites of highly porous and robust PEDOT-CNF by a simple and reproducible electrodeposition method ( Figure 1 d), and the experimental results showed that it has superior performance to pure PEDOT materials.…”
Section: Microelectrodesmentioning
confidence: 99%
“…( c ) Microscope image of the fishbone-shaped polyimide neural probe [ 55 ]. ( d ) Nanomaterials PEDOT-CNF to improve electrode performance: A—Optical micrograph of the neural probe; B—Schematic diagram of the PEDOT-CNF composite deposition [ 66 ]. Reprinted under a Creative Commons Attribution (CC BY) license.…”
Section: Figurementioning
confidence: 99%
“…As described in Figure 2a & b, we followed standard photolithographic and reactive ion etching procedures to achieve customizable well-defined ring-like electrode structures, patterned on a flexible and biocompatible parylene backbone. 34-35, 38-39 The photomask designs and etching parameters were optimised carefully during the microfabrication process, so that the gold electrode traces were revealed while avoiding the over etching of both parylene layers, which could enlarge the electrode surface area. All the four electrodes in HR microelectrode assembly were spanned in one direction and each probe consists of two different inner ring diameters (IRD) and surface areas (S.A), i.e., HR 445 (40 μm IRD and S.A. 445 μm 2 ) and HR 1400 (100 μm IRD and S.A.1400 μm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In parallel to the electrode geometry, new strategies utilizing rough organic conductive nanomaterials such a conductive polymers (e.g. PEDOT:PSS) 27-28 , carbon nanotubes (CNTs) 29 , carbon nanofibers (CNFs) 30-31 , graphene 32 , reduced graphene oxide (r-GO) 33 and their nanocomposites 34-36 have allowed to improve electrochemical surface area, while still providing the desired geometric area.…”
Section: Introductionmentioning
confidence: 99%
“…Amid the rapid advancement of electronics, bioelectronics, possessing characteristics of being lightweight, flexible, and DOI: 10.1002/adma.202310973 biocompatible, has gained prominence across research communities as it holds significant potential for the future landscape of flexible and wearable electronics, health monitoring and diagnostics, and the transformative enhancement of human-machine interaction. [1][2][3] In the past decades, there has been a consistent stream of newly developed advanced bioelectronic devices, including sensors, [4] recording probes, [5] organic transistors, [6,7] and biofuel cells [8,9] designed for tasks such as detecting important biomarkers, both stimulating and sensing cells and tissues, recording electrophysiological signals, and generating as well as storing energy. Among all electronic materials, the conducting polymer poly (3,4ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is often considered as a "king" material in bioelectronics due to its mixed electronic/ionic conductivity, flexibility, ease of processability, versatility, commercial availability, and believed biocompatibility.…”
Section: Introductionmentioning
confidence: 99%